Metal–Ligand Cooperative Proton Transfer/Electron Transfer and Acid-Assisted Protonation Mechanism for Mo-Catalyzed Reduction of Proton and Carbon Dioxide - Zhiyun Hu (17379685) (2025)
Density functional theory (DFT) study of Mo-catalyzed photoreduction of H+ and CO2 reveals a metal–ligand cooperative proton transfer/electron transfer (PT/ET) process and an intermolecular acid-assisted protonation mechanism. The key metal–hydride complex 23 pt-H is generated via two-electron-two-proton reduction of the initial catalyst Mo-2Hqpdt, where the redox noninnocent dithiolene ligand plays a crucial role in accepting and transferring electrons. In the generation of 23 pt-H, the one-electron reduction of 12 pt to 23 pt has a Gibbs energy barrier of 17.8 kcal/mol (14 → TSET2) and constitutes the overall rate-determining step for both H2 and HCOOH formation. The Mo–H moiety in 23 pt-H tends to be protonated by a carbonate molecule for the formation of H2, which presents a Gibbs energy barrier of 8.7 kcal/mol (213 → 2TS5). Alternatively, the Mo–H could also nucleophilically attack CO2 to form HCOOH, with a Gibbs energy barrier of 11.1 kcal/mol (23 pt-H → 2TS6’). Such a barrier difference of 2.4 kcal/mol could explain why H2 is the favored product in the experiments. The rate-determining step for CO formation is C–O cleavage with a total Gibbs energy barrier of 28.8 kcal/mol (14 → 2TS9), which is 11.0 kcal/mol higher than that of H2 and HCOOH; therefore, CO is a byproduct in the experiment. Moreover, intermolecular protonation rather than intramolecular protonation in 23 pt-H is confirmed as the pathway for H2 generation, which underscores the indispensable role of a small acid and provides valuable information for suppressing undesired hydrogen evolution.